HUBUNGAN BERAT LAHIR DENGAN KADAR ARAKIDONAT ACID PADA ASI DARI IBU MENYUSUI BAYI 1-4 BULAN DI KOTA MAKASSAR - Nur Nikmah Siradjuddin; Husnul Khatimah; Hijrah Asikin (Media Gizi Pangan, 2023)
Human milk is the most perfect food for babies, ideally breast milk is the only source of nutrition for six months at the beginning of life. This study aimed to assess the correlation levels of Arhacidonat Acid of breast milk in nursing mothers by birth weight (LBW and normal) in Makassar. Research conducted at the health center area of ​​Makassar. This type of research is observational analytic with cross-sectional design. How the sample selection using purposive sampling of 30 people, where the first group of 15 lactating mothers of normal birth weight babies and a second group of 15 mothers breastfeeding LBW infants. Levels of Arhacidonat Acid is checked by HPLC (Hight Performance Liquid Chromotography). Data were analyzed using SPSS using independent t-test to see relations birth weight infants with higher levels of essential fatty acids in milk both groups. Average levels of AA breastfed babies with normal birth weight lower than the levels of AA breastfeeding LBW infants (0.098 ± 0.006 mg / ml appeal of 0.085 ± 0.024 mg / ml) but the relationship was not significant (P> 0.05). It was concluded that there was no association between birth weight infants with higher levels of Arhacidonat Acid breast milk in lactating mothers of infants aged 1-4 months in Makassar.